2021
DOI: 10.1182/bloodadvances.2021004603
|View full text |Cite
|
Sign up to set email alerts
|

Humoral immune reconstitution after anti-BCMA CAR T-cell therapy in relapsed/refractory multiple myeloma

Abstract: Systematic and dynamic humoral immune reconstitution is little known for relapse/refractory (R/R) multiple myeloma (MM) patients who received anti-B-cell maturation antigen (BCMA) chimeric antigen receptor (CAR)-T cell therapy. We investigated the kinetics of B cell, normal plasma cell and immunoglobulin recovery in 40 patients who achieved ongoing response after anti-BCMA CAR-T cell therapy. All patients developed B-cell aplasia and the median duration of B-cell aplasia was 70 days (23-270). B cell count reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 39 publications
0
50
0
Order By: Relevance
“…Although, all patients who bridged to second-HSCT recovered normal immunoglobulin levels until the last follow-up. Wang et al investigated the kinetics of immunoglobin in 40 patients who received pre-HSCT CAR-T therapy and observed that the median times to IgG, IgM, and IgA recovery were 386 days, 254 days, and not reached during follow-up, respectively (27). Patients who received CAR-Ts after allo-HSCT in our study had more di culty in B-cell immune reconstitution than those who received CAR-Ts before allo-HSCT, suggesting that profound and lasting hypogammaglobulinemia cannot be resolved in patients who did not bridge to second-HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Although, all patients who bridged to second-HSCT recovered normal immunoglobulin levels until the last follow-up. Wang et al investigated the kinetics of immunoglobin in 40 patients who received pre-HSCT CAR-T therapy and observed that the median times to IgG, IgM, and IgA recovery were 386 days, 254 days, and not reached during follow-up, respectively (27). Patients who received CAR-Ts after allo-HSCT in our study had more di culty in B-cell immune reconstitution than those who received CAR-Ts before allo-HSCT, suggesting that profound and lasting hypogammaglobulinemia cannot be resolved in patients who did not bridge to second-HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Although patients receive intravenous immunoglobulin replacement to compensate for loss of normal B-cell or plasma cell function, some are prone to infection and exhibit long-term defects in humoral immunity. 35,36 In addition, neurotoxicity as an adverse effect of anti-CD19 therapy suggests "on-target, off-tumor" adverse effects likely due to CD19 expression on brain mural cells. 37 Antigen selection in solid tumors is more challenging than in hematological cancers because the "on-target, off-tumor" effects of solid tumor antigens often have more severe consequences in normal tissue function compared with B-cell aplasia (Fig.…”
Section: T Cell-intrinsic Limitationsmentioning
confidence: 99%
“…[39][40][41] One study showed that anti-BCMA CAR T cells caused a 7-month aplasia of normal BM plasma cells and a longer period of hypogammaglobulinemia. 42 Thus, protecting this patient population from infections is essential.…”
Section: Open Accessmentioning
confidence: 99%